Traumatic Brain Injury in the Elderly: Can We Reduce Readmissions?: A Community Hospital Experience. Issue 12 (December 2020) - Wasfie, Tarik; Maxwell, Jordan; Parsons, Andrea; Hille, Jennifer; Yapchai, Raquel; Hella, Jennifer; Cwalina, N; Barber, Kimberly R.; Shapiro, Brian
Background: Traumatic brain injury (TBI) is a leading cause of mortality and long-term morbidity in trauma patients, with a growing incidence among the elderly. Injury-related disability has many costs, and rehospitalization is a significant part of that. The current study was carried out in an elderly population with TBI to identify risk factors and measures associated with rehospitalization. Methods: We performed a retrospective analysis of 299 patients with a primary diagnosis of TBI admitted between 2016 and 2018. Variables selected for analysis encompassed the following: patient age, sex, comorbidities, diagnosis, length of stay, use of anticoagulants, 6-month readmission rate, and diagnosis for readmission. Chi-square analysis was used to identify potential risk factors, and multiple regression analysis was conducted to model the relationship. Results: 209 patients met inclusion criteria, with a mean age of 69 years (SD ± 18.6 years), with (51.5%) males and (48.5%) females. 188 (62.9%) patients were on anticoagulant therapy. 120 patients were discharged to home (40.1%). 79 patients (26.4%) were readmitted within 6 months of discharge, the majority of whom (48 patients, 60.8%) presented with a subdural hematoma (SDH). 38 readmitted patients (49%) came from home, and 57 patients (80%) were on anticoagulant therapy. Conclusion: In elderly patients with TBI, discharge to a home setting correlates with a higher risk of readmission within 6 months, a majority with a diagnosis of recurrent SDH. Anticoagulant therapy and frequent past readmissions also correlated with a higher risk of subsequent readmission.